2020
DOI: 10.1007/s10694-020-01017-6
|View full text |Cite
|
Sign up to set email alerts
|

Ignition and Burning of Fibreboard Exposed to Transient Irradiation

Abstract: Natural materials like wood are increasingly used in the construction industry, making the understanding of their ignition and burning behaviour in fires crucial. The state of the art of wood flammability is based mostly on studies at constant heating. However, accidental fires are better represented by transient heating. Here, we study the piloted ignition and burning of medium density fibreboard (MDF) under transient irradiation. Experiments are conducted in a Fire Propagation Apparatus under parabolic heat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…Studies on transient heat flux (Bilbao et al, 2002;Lizhong et al, 2007;Zhai et al, 2017;Gong et al, 2018;Santamaria and Hadden, 2019) have investigated time to ignition for transient as opposed to constant heat flux, including investigating the ignition criteria of critical temperature, critical heat flux, and critical mass flux; however, these studies have focused on incident radiative heating. Studies by Vermesi et al (2016Vermesi et al ( , 2017Vermesi et al ( , 2020 have investigated ignition of various materials exposed to transient heat fluxes and found that dual-criteria may be more accurate to describe ignition rather than a single criterion.…”
Section: Heat Flux At Ignitionmentioning
confidence: 99%
“…Studies on transient heat flux (Bilbao et al, 2002;Lizhong et al, 2007;Zhai et al, 2017;Gong et al, 2018;Santamaria and Hadden, 2019) have investigated time to ignition for transient as opposed to constant heat flux, including investigating the ignition criteria of critical temperature, critical heat flux, and critical mass flux; however, these studies have focused on incident radiative heating. Studies by Vermesi et al (2016Vermesi et al ( , 2017Vermesi et al ( , 2020 have investigated ignition of various materials exposed to transient heat fluxes and found that dual-criteria may be more accurate to describe ignition rather than a single criterion.…”
Section: Heat Flux At Ignitionmentioning
confidence: 99%
“…In the literature, the ignition of various timbers or wooden materials has been studied extensively to understand the initiation and growth of timber fires [10][11][12][13][14][15][16]. Like most flammable materials, the combustion limits and fire behaviors of timber materials can be influenced by both environmental (e.g., heating source, oxygen concentration, and wind velocity) and material (e.g., density, composition, moisture, and age) factors [17][18][19][20][21]. Moreover, timber, as a typical charring material, can sustain both flaming and smoldering combustion [13].…”
Section: Introductionmentioning
confidence: 99%
“…Emberley et al [9,15] further studied the self-extinction of flaming timber and CLT under external radiation and found the critical heat flux of 43.6 ± 4.7 kW/m 2 and the minimum mass flux of 3.93 ± 0.45 g/m 2 •s were required to sustain the flame. Vermesi et al [17] found that for engineered wood, the critical mass flux for flameout varied in a wide range (1.4-17 g/m 2 •s). Nevertheless, extinction of the flame is not the end of a fire, as it may be followed by the smoldering [31].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, solid wood results would be applicable to them. Vermesi et al [ 37 ] studied the ignition of fiberboards under transient irradiation. Surface temperatures at ignition were close to 300 °C for the majority of cases, with the exception being the parabolic flux, with a time to peak of 260 s and a peak irradiation of 30 kW∙m −2 .…”
Section: Resultsmentioning
confidence: 99%